Prevalence of anemia and its associated factors among female vegetarians in Kuala Lumpur and Selangor, Malaysia - Chai, Zi Fei (2018)
Vegetarianism has been gaining increased popularity worldwide over time due to a variety of reasons such as health, religion, and environmental impacts. However, vegetarians face the risk of nutritional disorders, such as anemia due to low dietary iron bioavailability and high phytic acid in their meal. Female vegetarians are at higher risk of anemia because of blood loss during menstruation or pregnancy. There is no published study on anemia problem among female vegetarians in Malaysia. Therefore, this cross-sectional study aimed to determine factors associated with anemia among female vegetarians in Kuala Lumpur and Selangor, Malaysia. Chinese and Indian vegetarians were recruited from a Buddhist and a Hindu organization, respectively. Height, weight, waist circumference (WC), and body fat percentage (BF%) of the respondents were measured by trained researchers. A 3-day 24-hour dietary recall was used to measure dietary intake of the respondents. Anemia status was assessed using blood hemoglobin (Hb) level, whereby 2ml venous blood samples were collected from the respondents by a qualified nurse. A self-administered questionnaire on sociodemographic background, lifestyle factors (smoking behavior, physical activity level, sleep quality), and psychological factors (depression, anxiety, stress) were completed by the respondents. A total of 177 female vegetarians (61.0% Chinese, 39.0% Indian) with a mean age of 48.4 years (SD=12.3 years) participated in this study. About half of the respondents (49.1%) were lacto-ovo-vegetarians, 27.7% were lacto-vegetarians, 18.1% were vegans, and 5.1% were ovo-vegetarians. The mean years of practicing vegetarianism among the respondents was 13.9 ± 9.9 years. Religion was the main reason for them to practice vegetarian diets (72.9%). Other reasons were health benefits (51.4%), environmental friendly (46.9%), animal welfare (39.0%), and family influences (7.9%). Results showed that the mean Hb of the respondents was 12.5 ± 1.1 g/dL, ranging from 8.7 to 15.4 g/dL. More than one in four of the respondents (28.2%) were anemic. About one third of the respondents were overweight (26.6%) and obese (5.6%), whereas 11.3% were underweight. Nearly half of the respondents (44.0%) were having abdominal obesity and 54.8% were having unhealthy body fat percentage (too high). More than half of the respondents did not meet the recommended nutrient intake (RNI) requirement for energy (59.3%), protein (56.5%), fat (56.6%), fiber (88.1%), vitamin B12 (99.4%), folate (90.4%), calcium (89.3%), and zinc (52.0%). None of the respondents were current smokers. More than half of the respondents (52.0%) had low physical activity level and 57.6% had poor sleep quality. In terms of psychological factors, 16.4% of the respondents were depressed, 37.3% were anxious, and 17.5% were stressed. Chi-square analysis results showed that age (χ2=11.793, p=0.008), marital status (χ2=6.281, p=0.012), the percentage of energy derived from protein (χ2=8.370, p=0.015), and vitamin C intake (χ2=4.268, p=0.039) were significantly associated with anemia. Furthermore, logistic regression analysis results showed that respondents with age below 50 years (AOR=2.53, 95% CI=1.24–5.19), who were married (AOR=2.79, 95% CI=1.31– 5.95), and who had inadequate intake of percentage of energy derived from protein (AOR=5.32, 95% CI=1.35–20.93) were found to be significantly associated with increased risk of anemia among female vegetarians in this study, in which they explained 16.4% of the variation in anemia status. In conclusion, the present study suggested that anemia is a public health problem among female vegetarians. Age, marital status, and percentage of energy derived from protein were significant factors associated with anemia. Future interventions may consider the strategies of increasing energy intake derived from protein among female vegetarians, especially in those who are married and aged below 50 years in order to increase the effectiveness of anemia prevention programs. More research need to be conducted to confirm these findings.